American knees - Wong, Shawn, 1949- (University of Washington Press, 2005)
"American Knees is a novel written by Shawn Wong, first published in 1995 by Simon & Schuster, and currently published by the University of Washington Press (2005). Conceived as a cultural response to Amy Tan's novel The Joy Luck Club, [citation needed] Wong's book depicts the love life of an Asian American man with three complex women. The book chronicles with humor the romantic chapters in the life of Raymond Ding, a Chinese American university administrator who first marries and divorces the perfect Chinese American wife, dates and breaks up with a hapa (bi-racial) younger woman, and gets involved with a Vietnamese American co-worker haunted by memories of the war